Methodological proposal for the incorporation of the clinical simulation cases to the system of teaching-learning methods in the Pediatric’s rotacional internship - Luis Alberto Corona Martínez; Mercedes Fonseca Hernández; Raúl López Férnandez; Nicolás Ramón Cruz Pérez (Medisur)
A methodological proposal is presented for the incorporation of the simulation of clinical cases (through the computer) to the system of teaching-learning’s methods in the Rotational Internship. The proposal is based in three elements: the full correspondence between the proposal; the current tendencies of the medical education; and the principal characteristics that govern the formation of general doctors in Cuba; the pedagogic value of the simulation like teaching method; and the possibilities that the computer offers as medium of teaching. The theoretical pattern is determined by the systemic focus of the teaching educational process; the concept of multiplicity of teaching methods; and the professor's outstanding rol in the process. In the proposal is defined how participate the different components of the educational process in the stay, in their reorganization in function of the incorporation of the simulation of cases; as well as the incorporation of some necessary methodological recommendations .The proposal has been applied during the year 2006-2007 and had a very good acceptance for the students. Although the proposal has been developed starting from the conditions of the stay of Pediatrics, it can be applied in anyone of the stays corresponding to the Rotational Boarding school, and even, in precedent years of the career framed in its clinical cycle.